Expect With Me: development and evaluation design for an innovative model of group prenatal care to improve perinatal outcomes - Shayna D. Cunningham; Jessica B. Lewis; Jordan L. Thomas; Stephanie A. Grilo; Jeannette R. Ickovics (BMC, 2017)
Abstract Background Despite biomedical advances and intervention efforts, rates of preterm birth and other adverse outcomes in the United States have remained relatively intransigent. Evidence suggests that group prenatal care can reduce these risks, with implications for maternal and child health as well as substantial cost savings. However, widespread dissemination presents challenges, in part because training and health systems have not been designed to deliver care in a group setting. This manuscript describes the design and evaluation of Expect With Me, an innovative model of group prenatal care with a strong integrated information technology (IT) platform designed to be scalable nationally. Methods/Design Expect With Me follows clinical guidelines from the American Congress of Obstetricians and Gynecologists. Expect With Me incorporates the best evidence-based features of existing models of group care with a novel integrated IT platform designed to improve patient engagement and support, enhance health behaviors and decision making, connect providers and patients, and improve health service delivery. A multisite prospective longitudinal cohort study is being conducted to examine the impact of Expect With Me on perinatal and postpartum outcomes, and to identify and address barriers to national scalability. Process and outcome evaluation will include quantitative and qualitative data collection at patient, provider, and organizational levels. Mixed-method data collection includes patient surveys, medical record reviews, patient focus groups; provider surveys, session evaluations, provider focus groups and in-depth interviews; an online tracking system; and clinical site visits. A two-to-one matched cohort of women receiving individual care from each site will provide a comparison group (n = 1,000 Expect With Me patients; n = 2,000 individual care patients) for outcome and cost analyses. Discussion By bundling prevention and care services into a high-touch, high-tech group prenatal care model, Expect With Me has the potential to result in fundamental changes to the health care system to meet the "triple aim:" better healthcare quality, improved outcomes, and lower costs. Findings from this study will be used to optimize the dissemination and effectiveness of this model. Trial registration ClinicalTrials.gov, NCT02169024 . Retrospectively registered on June 18, 2014.